2020
DOI: 10.3389/fpsyg.2020.01150
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, Alcohol Consumption and ADHD Symptoms in Adults

Abstract: Introduction: Substance use disorders and insomnia are common in the general population, and particularly among adults with attention-deficit/hyperactivity disorder (ADHD). Here we investigated the relationship between insomnia, alcohol consumption and ADHD symptoms.Methods: Adults with an ADHD diagnosis (n = 235, 41.3% males) and controls (n = 184, 38% males) completed a questionnaire assessing insomnia (Bergen Insomnia Scale), alcohol consumption (Alcohol Use Disorders Identification Test), and current ADHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
(84 reference statements)
0
4
0
1
Order By: Relevance
“…For example, a meta-analysis of thirteen cohort studies indicated that insomnia was associated with an increased risk of depression, anxiety and psychosis (Hertenstein et al ., 2019). Other longitudinal studies also reported that insomnia was strongly associated with future onset of ADHD (Liu et al ., 2020), BD (Lundervold et al ., 2020), PTSD (Neylan, 2013), MDD (Neylan, 2013), OCD (Alvaro et al ., 2017) and SCZ (Chung et al ., 2015). For chronotype, several cross-sectional studies suggested positive correlations of evening chronotype with MDD, BD, PTSD and SCZ (Kitamura et al ., 2010; Levandovski et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a meta-analysis of thirteen cohort studies indicated that insomnia was associated with an increased risk of depression, anxiety and psychosis (Hertenstein et al ., 2019). Other longitudinal studies also reported that insomnia was strongly associated with future onset of ADHD (Liu et al ., 2020), BD (Lundervold et al ., 2020), PTSD (Neylan, 2013), MDD (Neylan, 2013), OCD (Alvaro et al ., 2017) and SCZ (Chung et al ., 2015). For chronotype, several cross-sectional studies suggested positive correlations of evening chronotype with MDD, BD, PTSD and SCZ (Kitamura et al ., 2010; Levandovski et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another study also reported that a polygenic risk score accounting for 1.4% of the phenotypic variance in sleep duration was associated with the risk of depression (Dashti et al ., 2019). For insomnia, some cohort studies have suggested positive associations of insomnia with attention-deficit/hyperactivity disorder (ADHD) (Liu et al ., 2020), BD (Lundervold et al ., 2020), PTSD (Neylan, 2013), MDD (Ohayon and Roth, 2003), obsessive-compulsive disorder (OCD) (Alvaro et al ., 2017) and SCZ (Chung et al ., 2018). These associations between sleep-associated traits and psychiatric disorders may be to some extent affected by confounding or selection biases inherent in conventional observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…For ADHD, confounders such as body mass index, schizophrenia, alcohol consumption and other psychological symptoms (miserableness, neuroticism and frustration) were considered. [40][41][42] (Table S6).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Опитувальник BSAS використали G. D'Ettorre, V. Pellicani, A. Caroli, M. Greco (2020) для оцінки розладів сну в медсестер, які працюють позмінно [12]. A. J. Lundervold, D. A. Jensen, J. Haavik (2020) вивчали розлади сну в дорослих осіб з алкогольною залежністю [13]. I. S. Olufsen, M. E. Sørensen, B. Bjorvatn (2020) проводили дослідження серед пацієнтів із порушеннями сну, тривожністю та депресією [14].…”
Section: матеріали і методиunclassified